2020
DOI: 10.1186/s40594-020-00234-3
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of spatial skills and mathematics motivation on middle school mathematics achievement

Abstract: Background: Spatial skills and mathematical ability have been repeatedly identified as critical for achievement in Science, Technology, Engineering, and Mathematics (STEM). Previous studies have identified correlations between spatial skills and mathematical achievement; however, questions remain regarding improvements in non-spatial areas associated with STEM achievement. The current study examined whether competency in spatial skills could be related to individuals' motivation for mathematics. Measures of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 80 publications
1
25
0
3
Order By: Relevance
“…Their findings showed that students' mathematics performance improved following the classroom-based intervention and they claim that this was the first such study to find this in an elementary school setting. In a recent study, Atit et al (2020) examined the relationship between motivation for mathematics and spatial skills in middle school mathematics students and they found that both motivation and spatial skills interact significantly to predict student mathematics performance.…”
Section: Spatial Thinking In Schools and Collegesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings showed that students' mathematics performance improved following the classroom-based intervention and they claim that this was the first such study to find this in an elementary school setting. In a recent study, Atit et al (2020) examined the relationship between motivation for mathematics and spatial skills in middle school mathematics students and they found that both motivation and spatial skills interact significantly to predict student mathematics performance.…”
Section: Spatial Thinking In Schools and Collegesmentioning
confidence: 99%
“…We know that targeted spatial training can enhance spatial skills, but it is clear that enhanced spatial performance does not always correlate with success across all STEM disciplines. While spatial training has been shown to positively impact some aspects of academic performance, other variables are also at play including motivation (Atit et al, 2020), self-efficacy (Power & Sorby, 2020), and spatial anxiety (Atit et al, 2018).…”
Section: Spatial Thinking In Schools and Collegesmentioning
confidence: 99%
“…Moreover, this study did not collect precise gender breakdown of the participants and hence did not examine potential gender differences. It is noted that the gender representations from the respective schools were not visibly different, yet there remains room for exploring variables such as gender, as well as spatial skills and motivation, on students' geometry outcomes (Atit et al, 2020).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…In addition to this, spatial ability is quite important for the fields of science, technology, engineering, and mathematics (STEM) (Gilligan, Flouri & Farran, 2017;Kuhl, Lim, Guerriero & van Damme, 2019;Liu, Huang, Yu, & Dou, 2020). For instance, the results of the research conducted by Atit et al (2020), suggest that spatial skills play a significant role in middle school students' mathematics achievement. Delialioğlu and Aşkar (1999) determined that there is a positive, significant, and direct relationship between the spatial abilities of middle-school students and physics success.…”
Section: Introductionmentioning
confidence: 99%